COVID‐19 and inequities in colorectal and cervical cancer screening and diagnosis in Washington State. (18th March 2022) - Amram, Ofer; Amiri, Solmaz; Robison, Jeanne; Pflugeisen, Chaya Mangel; Monsivais, Pablo
Abstract: Introduction: Studies have shown that cancer screenings dropped dramatically following the onset of the coronavirus diseases 2019 (COVID‐19) pandemic. In this study, we examined differences in rates of cervical and colorectal cancer (CRC) screening and diagnosis indicators before and during the first year of the COVID‐19 pandemic. Methodology: We used retrospective data from a large healthcare system in Washington State. Targeted screening data included completed cancer screenings for both CRC (colonoscopy) and cervical cancer (Papanicolaou test (Pap test)). We analyzed and compared the rate of uptake of colorectal (colonoscopies) and cervical cancer (Pap) screenings done pre‐COVID‐19 (April 1, 2019–March 31, 2020) and during the pandemic (April 1, 2020–March 31, 2021). Results: A total of 26, 081 (12.7%) patients underwent colonoscopies in the pre‐COVID‐19 period, compared to only 15, 708 (7.4%) patients during the pandemic, showing a 39.8% decrease. A total of 238 patients were referred to medical oncology for CRC compared to only 155 patients during the first year of the pandemic, a reduction of 34%. In the pre‐COVID‐19 period, 22, 395 (10.7%) women were administered PAP tests compared to 20, 455 (9.6%) women during the pandemic, for a 7.4% reduction. period 1780 women were referred to colposcopy, compared to only 1680 patients during the pandemic, for a 4.3% reduction. Conclusion: Interruption in screening and subsequent delay in diagnosis during the pandemic will likely lead to later‐stage diagnoses for both CRC and cervical cancer, which is known to result in decreased survival. Impact: The results emphasize the need to prioritize cancer screening, particularly for those at higher risk. Abstract : Studies are showing that COVID‐19 had an impact on access to colorectal and cervical cancer screening. However, only limited number of studies focused on inequities in colorectal and cervical cancer screening during the pandemic and little has been reported on the impact on diagnosis. This study shows lower screening and diagnosis during COVID‐19, particularly for patients residing in rural areas.